2D Hybrid Perovskite Ferroelectric Enables Highly Sensitive X‐Ray Detection with Low Driving Voltage. (20th November 2019) - Ji, Chengmin; Wang, Sasa; Wang, Yaxing; Chen, Huaixi; Li, Lina; Sun, Zhihua; Sui, Yan; Wang, Shuao; Luo, Junhua
Abstract: X‐ray detectors with high sensitivity are of great significance in both civil and military fields. Over the past decades, great efforts have been made to improve the sensitivity in conventional inorganic materials, but mainly at the cost of increasing the energy consumption with a quite high operating voltage. Developing photosensitive ferroelectrics directly as detector materials may be a conceptually new strategy in view of the strong ferroelectric spontaneous polarization ( P s ) that assists photoinduced carriers separation and transport. A high‐performance X‐ray detector in 2D hybrid halide perovskite ferroelectric (C4 H9 NH3 )2 (C2 H5 NH3 )2 Pb3 Br10 (BA2 EA2 Pb3 Br10 ) ( P s = 5 µC cm −2 ) is fabricated and exhibits an ultrahigh X‐ray sensitivity up to 6.8 × 10 3 µC Gyair −1 cm −2 even at a relatively low operating voltage, which is over 300‐fold larger than that of state‐of‐the‐art α‐Se X‐ray detectors. Such a brilliant figure‐of‐merit is largely attributed to the superior mobility–lifetime products associated with the strong ferroelectric polarization of BA2 EA2 Pb3 Br10 . As pioneering work, these findings inform the exploration of hybrid halide perovskite ferroelectrics toward high‐performance photoelectronic devices. Abstract : A highly sensitive X‐ray detector employing a 2D hybrid perovskite ferroelectric (C4 H9 NH3 )2 (C2 H5 NH3 )2 Pb3 Br10 is fabricated. The device exhibits an ultrahigh sensitivity up to 6.8 · 10 3 µC Gyair −1 cm −2 .